COMMUNICATIVE LEARNING IN THE CLASSROOM INTERACTION (A DESCRIPTIVE STUDY ON THE TENTH GRADE STUDENTS IN MAN 3 TULUNGAGUNG IN THE 2016/2017 ACADEMIC YEAR) - Anis Azimah (JARES (Journal of Academic Research and Sciences), 2017)
This research aims at observing how the process of communicative learning occurred in the classroom interaction and identifying the types of interaction in the classroom. To meet the purposes of the research, this research raised the questions related to the principal features of Communicative Orientation of Language Teaching (COLT) scheme proposed by Nunan (1992). MAN 3 Tulungagung was taken as the setting of the research. The interaction between English teacher and students of Acceleration (X-10) class in the 2016/2017 academic year were recorded as the subject of the analysis. To examine the learning process and interaction, this research used qualitative approach in the form of descriptive method. In collecting the data, the researcher employed video recording. The data obtained through the observation was in the form of transcribed interaction. It was also found that the types of interaction occurred in the classroom are Teacher-Class (T - C), Teacher-Group (T-G), Teacher-Student(s) (T-S), and Student-Student (S-S) interactions. Each of this interaction is influential in the classroom. Regarding the findings of the research, the researcher concludes that these communicative analysis can be used as self-monitoring for English teacher to create communicative classroom. Therefore, this study is useful to introspect teacher ’s and learner ’s performance in the classroom. Key words: communicative Learning, Classroom Interaction.